(untitled) (Journal of actual problems of jurisprudence, 2019)
In given article theoretical questions of features of civil legal proceedings which is discussed in a science of a civil procedural right throughout all history of its development are considered. One authors try to give the developed substantial characteristic of civil process, to open structure of its basic components. Representatives of other point of view consistently defend idea of diffi cult structure of the civil process, based on the detailed analysis of character of communication between remedial activity and remedial relations in civil process.